MODELLING OF LATE TYPE SPECTRA AND ABUNDANCES: NEW OBSERVED DATA AND APPROACHES - Pavlenko, Ya. V.; Jenkins, J. S.; Jones, H. R.A. (Одеські астрономічні публікації, 2010)
Spectrum of well known solar twins are interested for us in many aspects. We test the use the minimisation procedure to the observed spectrum of the Sun (Kurucz et al. 1996) in the wide spectral region λλ 4000 -8700 Å . For the Sun we obtained log N(fe) = -4.40, i.e the reference abundance (Gurtovenko & Kostik 1989), and microturbulence velocity Vt = 1 km/s